Direct hydrogenation of amides to alcohols and amines under mild conditions - Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Shimon, Linda J. W.; Milstein, David (Journal of the American Chemical Society, 2010)
The selective, direct hydrogenation of amides to the corresponding alcohols and amines with cleavage of the C−N bond was discovered. The expected products of C−O cleavage are not formed (except as traces in the case of anilides). The reaction proceeds under mild pressure and neutral, homogeneous conditions using a dearomatized, bipyridyl-based PNN Ru(II) pincer complex as a catalyst. The postulated mechanism involves metal−ligand cooperation by aromatization−dearomatization of the heteroaromatic pincer core and does not involve hydrolytic cleavage of the amide. The simplicity, generality, and efficiency of this environmentally benign process make it attractive for the direct transformations of amides to alcohols and amines in good to excellent yields.

Direct synthesis of secondary amines from alcohols and ammonia catalyzed by a ruthenium pincer complex - Balaraman, Ekambaram; Srimani, Dipankar; Diskin-Posner, Yael; Milstein, David (Catalysis Letters, 2015)
Efficient and selective direct synthesis of secondary amines from primary alcohols and ammonia with liberation of water has been achieved, with high turnover numbers and with no generation of waste. In case of benzylic alcohols, imines rather than amines are obtained. This atom economical, environmentally benign reaction is homogenously catalyzed by a well-defined bipyridine based Ru(II)-PNN pincer complex.
Keywords: Alcohol; Ammonia; Homogenous catalysis; Ru-pincer complex; Secondary amine

Direct access to N-alkylated amines and imines via acceptorless dehydrogenative coupling catalyzed by a cobalt(ii)-NNN pincer complex - Midya, Siba P.; Pitchaimani, Jayaraman; Landge, Vinod G.; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
A simple, phosphine-free Co(ii)-NNN pincer complex catalyzed direct N-alkylation of anilines with alcohols via hydrogen auto-transfer (HA) and selective acceptorless dehydrogenative coupling (ADC) of benzylamines with alcohols affording imines with the liberation of molecular hydrogen and water is reported.

Dehydrogenative coupling of alcohols with internal alkynes under nickel catalysis: an access to β-deuterated branched ketones - Subaramanian, Murugan; Gouda, Chandrakant; Roy, Triptesh Kumar; Ganesan, Sivakumar; Banerjee, Subhrashis; Vanka, Kumar; Balaraman, Ekambaram (ACS Catalysis, 2024)
In synthetic organic chemistry, unconventional strategies for advanced chemical synthesis pose interesting and challenging problems. Alcohols act as alkylating agents in the C-C and C-N bond-forming reactions via the dehydrogenative borrowing hydrogen strategy in traditional transition metal catalysis; however, as an acylating agent in the C-C bond-forming reactions is challenging and rarely reported. Here, we report the dehydrogenative coupling of benzylic alcohols with internal alkynes under nickel(II) catalysis, wherein alcohol is used as an acylating agent. This reaction system affords a wide range of alpha-branched aryl ketone derivatives with zero waste generation through the umpolung borrowing hydrogen strategy. Moreover, we have demonstrated the chemodivergent applications of the alpha-disubstituted ketones to other valuable building blocks, including large-scale synthesis of beta-deuterated branched ketones. Several spectroscopic studies, intermediate identification, and density functional theory calculations were performed to elucidate the reaction mechanism.
Keywords: Alcohols; alpha-branched aryl ketones; dehydrogenative coupling; internal alkynes; nickel catalysis; pseudoumpolung